Pengaruh Persepsi Harga, Orientasi Merek, dan Orientasi Belanja terhadap Niat Beli Fashion Online - Ivoni, Dzara; Santika, I Wayan; Suryani, Alit (E-Jurnal Manajemen, 2015)
Online shopping has become a trend and business phenomenon today in Indonesia. Purchase intention is a mental state that reflects consumers plan to purchase a number of products. This study aims to determine the effect of price perception, brand orientation, and shopping orientation of the intention to buy fashion online to students in the city of Denpasar. By using multiple linear regression analysis method, the results showed that simultaneous perception variable price, brand orientation, and shopping orientation and significant positive effect on the intention to buy fashion online. Partially shows that the perception of variable pricing and shopping orientation and a significant positive effect on the intention to buy fashion online. As for the brand orientation variable is positive and not significant effect on the intention to buy fashion online at students in the city of Denpasar.
Keywords: perceptions of price; brand orientation; shopping orientation; purchase intention; online shopping